THE PLACE OF CREATION OF NAIM KARIMOV IN THE DEVELOPMENT OF THE STUDIES OF OYBEK (Scientific journal of the Fergana State University, 2023)
The contributions of Naim Karimov to the development of Oybek`s writing by the book “Oybek”. The peculiarities of Naim Karimov`s style are investigated.